2022
DOI: 10.1016/j.tra.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A double jeopardy: COVID-19 impacts on the travel behavior and community living of people with disabilities

Abstract: The COVID-19 pandemic response has had a significant impact on the general population’s ability to participate in their communities. Individuals with disabilities, an already socially disadvantaged population, are more vulnerable to and have likely been disproportionately impacted by COVID-19 response conditions. Yet, the extent to which daily community living activities of people with disabilities have been impacted is unknown. Thus, this study assesses their travel behavior and community living during the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…At the individual-level, Astroza et al (2020) used questionnaire data from a sample of 4395 adults in Chile, and found that females and the elderly are more likely to work from home and thus have lower public transit use like metro use. Park et al (2022) employed survey data and reported that individuals with disabilities were particularly vulnerable during the pandemic as they relied more on public transit and lacked access to alternative transportation modes. Park and Cho (2021) used individual-level smart card data in Korea, which included both senior citizen card and ordinary card, and found that the elderly's fear of COVID-19 was the strongest because of the high fatality rate among the elderly, resulting in the most prominent reduction in metro use among the elderly aged 65 years and over.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…At the individual-level, Astroza et al (2020) used questionnaire data from a sample of 4395 adults in Chile, and found that females and the elderly are more likely to work from home and thus have lower public transit use like metro use. Park et al (2022) employed survey data and reported that individuals with disabilities were particularly vulnerable during the pandemic as they relied more on public transit and lacked access to alternative transportation modes. Park and Cho (2021) used individual-level smart card data in Korea, which included both senior citizen card and ordinary card, and found that the elderly's fear of COVID-19 was the strongest because of the high fatality rate among the elderly, resulting in the most prominent reduction in metro use among the elderly aged 65 years and over.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increasing number of empirical studies have substantiated the change of city-level or station-level metro transit ridership due to the pandemic and mobility policies ( Chang et al, 2021 ; Jiang & Cai, 2022 ; Kwon et al, 2022 ). However, only a limited number of studies have investigated the change of individual-level metro use behaviors, including metro trip frequency, travel time, and mode shift from metro to private cars ( Astroza et al, 2020 ; Park & Cho, 2021 ; Park et al, 2022 ; Maljaee & Sameni, 2022 ). The individual-level research, which is needed more, can help policymakers identify vulnerable socioeconomic groups and disadvantaged groups in metro use during and post the pandemic, promoting effective and equitable mobility intervention policies ( Park et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations